Floor systems for implementing monetary policy: Some unpleasant fiscal arithmetic - Aleksander Berentsen; Alessandro Marchesiani; Christopher J. Waller (University of Zurich, Department of Economics, 2013)
An increasing number of central banks implement monetary policy via a channel system or a floor system. We construct a general equilibrium model to study the properties of these systems. We find that the optimal framework is a floor system if and only if the target rate satisfies the Friedman rule. Unfortunately, the optimal floor system requires either transfers from the fiscal authority to the central bank or a reduction in seigniorage payments from the central bank to the government. This is the unpleasant fiscal arithmetic of a floor system. When the central bank faces financing constraints on its interest expense, we show that it is optimal to operate a channel system.
Keywords: E52; E58; E59; 330; monetary policy; floor system; channel system; standing facilities